PENGEMBANGAN BAHAN AJAR PAI BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN PEMAHAMAN SISWA TENTANG ISLAM RAHMATAN LIL ‘ALAMIN - Ali, Moh. (Andragogi: Jurnal Pendidikan Islam dan Manajemen Pendidikan Islam, 2025)
Islamic Religious Education (PAI) in Indonesia faces challenges in instilling a deep and relevant understanding of Islamic teachings, especially the concept of Islam Rahmatan lil 'Alamin, amidst globalization and cultural diversity. A comprehensive understanding of Islam as a blessing for the universe is crucial to building students' tolerant, moderate, and peace-loving characters. This study aims to develop a conceptual framework for PAI teaching materials that integrate the values of Indonesian local wisdom to improve students' understanding of Islam Rahmatan lil 'Alamin. The research method used is a qualitative literature study, by analyzing and synthesizing data from various relevant literature sources provided, including scientific journal articles, theses, and guidance documents. The results of the analysis indicate the potential for strong synergy between the objectives of PAI, the noble values in local wisdom of the archipelago (such as mutual cooperation, deliberation, tolerance, justice, and social and environmental harmony), and the essence of Islam Rahmatan lil 'Alamin. Identification of various examples of local wisdom from various regions, such as the Ngejot tradition in Lombok, Metabe' in Mandar, the values of Sipakatau, Sipakalebbi, Sipakainge' in Bugis, and Maja Labo Dahu in Bima, show alignment with universal Islamic values. Integration of this local wisdom into Islamic Religious Education teaching materials, through active, participatory, and contextual learning strategies—in line with the theory of Contextual Learning (CTL)—is identified as a promising approach. The proposed Contextual-Integrative Islamic Religious Education Teaching Materials Based on Local Wisdom (PAIKIB-RL) model has the potential to increase the relevance of Islamic Religious Education learning, strengthen students' cultural identity, and significantly deepen their understanding of Islam Rahmatan lil ‘Alamin. This study has implications for the need for innovation in the development of Islamic Religious Education curriculum and teaching materials, increasing teacher capacity, and further research for empirical validation of the proposed model